Just One Click Away: The Politics of E‐Commerce Sales Tax Policy. Issue 1 (27th September 2016) - Bjorklund, Eric
Abstract : E‐commerce has altered the relationship between consumers, businesses, and U.S. states. E‐retailers are not required to collect sales tax from their customers, thus depriving fiscally insecure states of tax revenue, and providing a competitive advantage for e‐retailers, like Amazon Inc., in their struggle for market share with brick‐and‐mortar stores, like Walmart. Attempts at e‐commerce sales tax policy by state legislators and brick‐and‐mortar lobbyists failed until 2008 when New York successfully passed legislation. A subsequent wave of legislation ensued, and between 2008 and 2012, e‐commerce sales tax legislation left committee in fourteen states, each experiencing various levels of success. Existing explanatory efforts have not fully accounted for the combinatorial effect of political–institutional structure and market contestation in U.S. state‐level policy creation, as well as the likelihood of multiple pathways to passage. Embracing this framework, I use fuzzy set Qualitative Comparative Analysis (fsQCA) to uncover three sufficient pathways for successful passage of e‐commerce sales tax policy. Two paths highlight the confluence of large retailer pressure and a conductive political–institutional structure facing fiscal stress, while the third path reflects political–institutional forces. These findings corroborate, as well as build upon, our knowledge of fiscal sociology, policy domains, and corporate power in American politics.